Voicing in Contrast. Acquiring a Second Language Laryngeal System - Simon, Ellen (Academia Press, 2010)
Drawing on both rule-based and constraint-based approaches, Voicing in Contrast examines typological differences in the laryngeal systems of Dutch and English and investigates the extent to which native speakers of Dutch acquire English obstruent voicing. The analysis is based on a substantial new data collection of conversational Dutch and English speech by speakers of different varieties of Dutch. The results of the study show that the English interlanguage of advanced learners contains a mixed laryngeal system with elements from Dutch as well as from English. The book discusses how this system could emerge and analyses the extent to which learners succeeded in suppressing neutralizing processes of devoicing and voice assimilation. The results of the empirical analysis are examined in the light of existing theoretical approaches to laryngeal systems. Although the focus is on Dutch and English, the frequent references to other languages invite the reader to carry out comparable analyses for other languages with similar laryngeal systems. A detailed description of the methodology also makes the book of interest to scholars working with large databases of spoken first and second language speech. A sample of the data is available on a CD-rom accompanying the book.